Mutual Coupling Reduction of Super Wide Band MIMO Antenna Using Metamaterial Periodic Defected Ground Structures for THz Applications - Tomar, V.K.; Ranjana Kumari (International Journal of Integrated Engineering, 2024)
In this article, a double negative (DNG) material inspired periodic defected ground structure is presented to reduce mutual coupling and gain enhancement of super wide band multiple input and multiple output antenna (SWBMA) for terahertz (THz) applications. For THz applications, a dual port super wide band MIMO antenna with size of 0.35 λ0 ×0.17 λ0 ×0.02 λ0 (57 ×27.6 ×3.36 µm3) has been designed on quartz substrate. The simulated results of proposed antenna exhibit fractional bandwidth (FWB) of 164% at 9.9THz resonant frequency (1.75 to 18THz) with peak gain 9.2dBi, and average radiation efficiency 89% throughout the super wide band spectrum. By inserting DNG meta-material based periodic defected ground structures in between inverse L stubs on ground plane, an isolation S12/S21 between radiating elements of Si,j ≤ -25dB has been attained. MIMO parameters of designed antenna are also investigated and it is observed that ECC9.98 dB, TARC